Leisure as a space of political practice in Middle East women life writings - Asl, Moussa Pourya (Penerbit Universiti Kebangsaan Malaysia, 2019)
Middle East women’s active participation in resisting against socio-political impositions and constraints has received scant attention in the existing scholarship within the field. Much of the literature is focused on the socially victimized, subjugated and passive state of the female subjects in facing patriarchal authoritarianism and repression. In contrast, this article aims at exploring the subjected women’s investment in multifarious acts of resistance through their leisure time and practices. To this end, Foucault’s notion of “counter-conduct,” a mode of resistance to be governed differently, is used to examine women’s leisure activities in Jean P. Sasson’s (1992) Princess: A True Story of Life Behind the Veil in Saudi Arabia, Azar Nafisi’s (2003) Reading Lolita in Tehran and Manal al-Sharif’s (2017) Daring to Drive. The analysis of these narratives within the power/resistance framework underlines the shifting complexities of the female participants’ life course, and reveals that the subjugated women’s trajectory in the stories is a gradual progression from pure submissiveness towards an active engagement in social, cultural and political realities. Throughout the narratives, women use leisure time and activities such as driving, reading and bonding in parallel to dominant techniques of governmentality to produce alternative subjectivities. The study concludes that the life accounts do not merely provide an oversimplified depiction of Middle East women as passive victims of a misogynistic cultural tradition, but rather chronicle women’s active protests—i.e., individual and collective revolts of conduct, acts of opposition and violations of established norms—similar to the forms of counter-conduct theorized by Foucault.